The relevancy of caning as a form of criminal punishment in Malaysia / Mohd Fared Bahtar…[et al.] - Bahtar, Mohd Fared; Idris, Mohd Nasri; Awang Mat Isa, Mohamad Saiful Idham; Md Rijani, Muhammad Hafiz Muim (2009)
In Malaysia, corporal punishment by caning/whipping has been used for decades, mostly as an additional sentence to imprisonment or as an alternative to a fine. There are four statutes that govern the sentences of whipping namely The Penal Code, the Arms Act 1960, the Firearms (Increased penalty) Act 1971, and Dangerous Drugs Ordinance 1952. There are three categories of persons who cannot be imposed the sentence of whipping, namely females, males sentenced to death, and males whom the court considers to be more than fifty years of age. In recent events, questions has been put forward by the human rights movement that this form of punishment is rather harsh and inhumane. There has been a doubt on whether it is still relevant as a form of criminal punishment to be practised in this country. Some people view it as a rather uncivilized form of punishment rather than to rehabilitate, to deter, to reform and as retribution in accordance with the four theories of punishment highlighted by the jurist. Caning/whipping or known as " Al-Jald" has also been a part of Islamic law on sentencing, and divided into two categories, whipping as provided for hudud offences and whipping for ta'zir offences. There has been a numbers of hadith and verse in the holy Al-Quran which approved the validity of whipping as a form of punishment in Islam. Therefore it can be conclude that in Islam, caning/whipping is acknowledge as a form of punishment.